Dance Learning for Deaf Children Through Metaphoric Activities - Sandi Jembar Wijaya; Juju Masunah; Reni Haerani (Gondang: Jurnal Seni dan Budaya, 2023)
Hearing problems in deaf children make it difficult for them to absorb verbal information while learning, but their learning modalities can be optimized. In the dance learning process at SLB Tunas Kasih 1 Bogor, the teacher stimulates deaf children to create their own dance moves through metaphorical activities based on the surrounding environment by optimizing visual and tactile learning modalities. The purpose of this article is to describe learning dance through metaphorical activities for deaf children at SLB Tunas Kasih 1 Bogor. This study uses a qualitative approach with descriptive analysis method. The data sources for this research were teachers and deaf children at SLB Tunas Kasih 1. Data collection used observation, interviews and documentation studies. Data analysis was carried out by means of triangulation. The results of this study indicate that through metaphorical activities, children can maximize their visual and tactile abilities in obtaining information in dance lessons so that learning can match the abilities of deaf children. Metaphoric activities also foster imaginative ideas, making it easier for them to explore dance movements resulting from their ideas. Through this metaphoric activity the teacher can easily foster the creativity of deaf children in creating dance movements, so that deaf children can optimize their creative abilities for dance moves.